Coated glass substrates and methods of making same
By forming alternately arranged silver infrared reflective functional layers and dielectric coatings on the glass substrate, and diffusing silver nanoparticles using ion implantation technology, the problem of insufficient chemical resistance of existing coated glass substrates is solved, and higher durability and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202380063511.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-05
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-11
AI Technical Summary
The existing coated glass substrates have limited chemical resistance and are difficult to maintain performance in chemically corroded environments.
By forming an alternately arranged silver infrared reflective functional layer and a dielectric coating on the glass substrate, and using ion implantation technology, silver nanoparticles are diffused in the dielectric coating, thereby improving the chemical resistance of the coating.
Significantly improves the chemical resistance of the coating, can show better durability in climate chambers and salt spray tests, reducing defects in the coating.
Smart Images

Figure CN119816477A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to coated glass substrates which comprise a silver layer and have improved chemical resistance. The present invention also relates to a method for producing such a coated glass substrate.
[0002] The coated glass substrate of the invention can be used as thermal insulation glazing and / or solar control glazing. These glazings are intended to be installed both in buildings and in vehicles. Their purpose is in particular to reduce the air conditioning load and / or to reduce excessive overheating (so-called "solar control" glazing) and / or to reduce the amount of energy lost to the outside (so-called "low-e" glazing). Background Art
[0003] A large number of coatings used on glass substrates rely on one or more silver-containing layers to provide reflection of infrared light in order to enhance the thermal insulation and / or solar control properties of the glazing. Such silver-containing layers are typically sandwiched between dielectric coatings that include one or more separate oxide, nitride, or oxynitride layers that help protect the silver layer and improve the optical properties (particularly in terms of desired reflectivity and color). The chemical resistance of such glazing is often improved by adding certain layers, such as layers containing silicon nitride or mixed oxides of zinc and tin, over the silver layer.
[0004] US20208139935 A1 discloses a multilayer coating of alternating metal hydride nitride layers and one or more silver layers, in which Ag nanoparticles of undisclosed size are diffused from the underlying Ag layer into the overlying dielectric by thermal or optical treatment, resulting in improved conductivity. Here, Ag diffusion occurs almost throughout the overlying dielectric, no improvement in chemical resistance is shown, and the nanoparticle size is not reported.
[0005] It has been found that these coatings still have limited chemical durability. Summary of the invention
[0006] It is an object of the present invention to provide coated glass substrates having good chemical resistance.The present invention relates in particular to coatings on glass substrates, these coatings comprising one or more layers deposited by magnetron sputtering.
[0007] The invention is based on the discovery that the chemical resistance of a coated glass substrate can be significantly improved by subjecting it to ion implantation, wherein the coating comprises n infrared-reflecting functional layers comprising silver and n+1 dielectric coatings arranged alternately, wherein n≥1, such that each functional layer is surrounded by a dielectric coating and at least one dielectric coating is in direct contact with at least one infrared radiation-reflecting functional layer. It was found that the at least one dielectric coating in direct contact with at least one infrared radiation-reflecting functional layer comprises silver nanoparticles having a diameter in the range of 1 to 5 nm at a distance of up to 10 nm from the infrared radiation-reflecting functional layer. The coating according to the invention maintains electrical conductivity.
[0008] The present invention therefore relates to a glazing comprising a glass substrate and comprising a coating on at least one main surface of the glass substrate, the coating comprising n infrared radiation reflecting functional layers comprising silver and n+1 dielectric coatings arranged alternately, wherein n≥1, so that each functional layer is surrounded by a dielectric coating, wherein at least one dielectric coating is in direct contact with at least one infrared reflecting functional layer and comprises silver nanoparticles having a diameter in the range of 1 to 5 nm at a distance of up to 10 nm from the at least one infrared reflecting functional layer.
[0009] The presence of silver nanoparticles has been confirmed by transmission electron microscope (TEM) images taken of the cross sections of the coated substrates. The nanoparticles appear to be substantially circular, and the diameter is the cross-sectional equivalent diameter as determined on the TEM image. If the nanoparticles have an irregular shape, then the cross-sectional equivalent circular diameter is the diameter of a two-dimensional disk having an equivalent area to the cross section of the nanoparticles, such as determined by an image analysis method. TEM images can be, for example, processed with image analysis software ImageJ (developed by the National Institutes of Health) to determine, for example, particle size.
[0010] To our knowledge, ion implantation may play a dual role in the formation of silver nanoparticles, firstly by enhancing the diffusion of silver into the surrounding layers and secondly by providing mobility to the components of the layers, thereby allowing the silver to reorganize into larger nanoparticles.
[0011] For the sake of clarification, the fact that the silver nanoparticles are found at a distance of up to 10 nm from the infrared radiation reflecting functional layer means that they are at most found at a distance of up to 10 nm, but not more than 10 nm.
[0012] The present invention further relates to a method for improving the corrosion resistance of a coated glass substrate. The method may include the following operations: a. providing a glass substrate comprising a coating on a major surface, the coating comprising n infrared radiation reflecting functional layers comprising silver and n+1 dielectric coatings arranged alternately, wherein n≥1, such that each functional layer is surrounded by a dielectric coating, wherein at least one dielectric coating is in direct contact with at least one infrared reflecting functional layer; b. Providing a source gas selected from O2 or N2, He, Ne, Ar or Kr; c. ionizing the source gas to form ions of O, N, He, Ne, Ar or Kr; d. Accelerate O, N, He, Ne, Ar or Kr ions with a certain accelerating voltage to form an ion beam, e. Positioning the glass substrate component in the trajectory of a beam of ions of O, N, He, Ne, Ar or Kr, with the coating facing the beam and setting the acceleration voltage to a value of at least 5 kV and 100 kV so as to implant the ions throughout the at least one infrared reflecting functional layer.
[0013] Advantageously, the accelerating voltage is set to a value selected between 5 kV and 100 kV. Accelerating voltages greater than 100 kV may also be successful, but may result in a more complicated implantation device. More advantageously, the accelerating voltage is set to a value of at least 10 kV, even more advantageously at least 12 kV. It was found that accelerating voltages above 100 kV result in rapid and complete degradation of the functional layer containing silver.
[0014] In a preferred embodiment, the ions of O, N, He, Ne, Ar and KR are positively charged ions.
[0015] The invention further relates to the use of implanting ions for improving the corrosion resistance of a glass substrate, the glass substrate comprising a coating on at least one main surface thereof, the coating comprising n infrared radiation reflecting functional layers comprising silver and n+1 dielectric coatings arranged alternately, wherein n≥1, so that each functional layer is surrounded by a dielectric coating, wherein at least one dielectric coating is in direct contact with at least one infrared reflecting functional layer.
[0016] It is to be understood that in the context of the present invention, the chemical resistance of a coated glass substrate is the chemical resistance of a coating on a glass substrate as demonstrated using the climate chamber and neutral salt spray tests as described below.
[0017] The coating of the invention may have a total geometric thickness T of up to 300 nm. The total thickness T is preferably between 10 and 200 nm, more preferably between 20 and 100 nm and in particular between 40 and 70 nm.
[0018] In certain embodiments, the coatings of the present invention may be solar control or thermal insulation low-E coatings.
[0019] According to an embodiment of the present invention, the coating preferably includes n infrared radiation reflecting functional layers and n+1 dielectric coating layers arranged alternately, wherein n=1, n=2 or n=3.
[0020] According to an embodiment of the invention, one or more layers or in particular all layers of the multilayer stack are deposited by magnetron sputtering.
[0021] In the coating of the invention, the infrared radiation reflecting functional layer is a layer containing silver, which can consist of silver or can be doped with palladium or gold, for example, in a proportion of up to 5% by weight, preferably about 1% by weight. The incorporation of small amounts of dopants into the silver-based layer can improve the chemical stability of the stack.
[0022] The inventors have discovered that in chemical resistance testing, defects are often associated with delamination occurring at the interface between the silver-based layer and the contact layer (eg, dielectric layer). DETAILED DESCRIPTION
[0023] The infrared radiation reflecting functional layer advantageously has a thickness of at least 6nm or at least 8nm, preferably at least 9nm. Their thickness is preferably at most 22nm or at most 20nm, more preferably 18nm. These thickness ranges can make it possible to achieve desired low emissivity and solar control functions while maintaining good light transmittance. In the coating stack with two functional layers, it may be preferred that the thickness of the second functional layer farthest from the substrate is slightly greater than the thickness of the first functional layer, to obtain better selectivity. In the case of the coating stack with two functional layers, the first functional layer may have, for example, a thickness between 8 and 18nm, and the second functional layer may have a thickness between 10 and 20nm.
[0024] In the coating of the invention, the dielectric coating may comprise one or more layers each made of a dielectric material of the metal nitride, metal oxide or metal oxynitride type. From an optical point of view, the purpose of these coatings surrounding the metal functional layer is to "anti-reflect" this metal infrared reflective functional layer.
[0025] In the multilayer stack of the present invention, a sacrificial metal or sub-oxidized barrier layer may be arranged in contact with one or more infrared reflecting functional layers above and / or below the functional layers to prevent them from degrading during the deposition process and / or during tempering or bending. For the purposes of the present invention, such sacrificial barrier layers are not considered to be part of the dielectric coating.
[0026] In the multilayer stack of the present invention, a dielectric seed layer or barrier layer, in particular a zinc oxide layer, advantageously an aluminum-doped zinc oxide layer, can be deposited by magnetron sputtering so as to be in direct contact with one or more infrared-reflecting functional layers above and / or below the functional layers to promote the crystal growth of the metallic functional layers (seed layer) and / or to prevent them from degrading during the deposition process and / or during tempering or bending (barrier layer). For the purposes of the present invention, these dielectric seed layers or barrier layers are considered to be part of the corresponding dielectric coating above or below the functional layers.
[0027] The multilayer stack in the present invention may be part of a larger multilayer coating where additional layers are added after ion implantation into the multilayer stack.
[0028] When referring to implantation depth, it should be understood that the depth is measured from the outer surface of the coating toward the bulk of the substrate. In addition, the maximum depth Dmax of the implanted ions may be greater or less than the thickness T of the coating.
[0029] Figure 1 A schematic diagram of a glass substrate (6) is shown, which includes a coating (7) on at least one main surface, the coating including n=1 infrared radiation reflecting functional layers (2) containing silver and n+1=2 dielectric coatings (1, 3) arranged alternately, the functional layers (2) being surrounded by the dielectric coatings (1, 3). Both dielectric coatings (1, 3) are in direct contact with the infrared reflecting functional layers (2) and contain silver nanoparticles (4, 5) at a distance of up to 10 nm from the infrared reflecting functional layers (2), the silver nanoparticles (4, 5) having a diameter in the range of 1 to 5 nm.
[0030] In general, but not limited to the description of the present invention, the glass substrate can generally be soda-lime silicate glass, in particular transparent or extra-transparent glass. However, as will be appreciated by those skilled in the art, the substrate can be other types of glass, such as borosilicate glass or alumina silicate glass. The glass substrate can also be colored or absorptive, or even almost opaque in the visible light range.
[0031] In an embodiment, the glazing according to the invention comprises implanted ions in the coating selected from ions of O, N, He, Ne, Ar or Kr. It was found that heavier ions lead to a rapid and complete degradation of the functional layer comprising silver.
[0032] The implanted ions are preferably positively charged ions.
[0033] The implantation ions are implanted into the coated substrate preferably starting from the outer surface of the coating to a depth Dmax comprised between 0.1 μm and 1 μm.
[0034] The amount or dose per surface unit of implanted ions is preferably comprised between 5×1014 ions / cm 2 with 10 18 ions / cm 2 between 10 16 ions / cm 2 With 5×10 17 ions / cm 2 between 3×10 16 ions / cm 2 with 10 17 ions / cm 2 The ion dose can be controlled, for example, by the duration of exposure to the ion beam and also depends on the ion current of the ion beam. At lower doses, no durability improvement may be observed. At higher doses, the coating may be damaged.
[0035] It has been unexpectedly discovered that implanting ions can reduce the amount of defects that appear in the coating, particularly in the durability testing described below.
[0036] In an embodiment of the present invention, the trajectory of the ion beam is substantially perpendicular to the surface of the glass substrate.
[0037] In certain embodiments, the glass substrate is moved relative to the ion beam so that the entire surface of the glass substrate is processed in a single pass or in multiple passes.The glass substrate member may be moved at a speed comprised between 20 and 160 mm / s.
[0038] The inventors have found that, advantageously, an ion source that provides an ion beam containing a mixture of singly charged ions and multiply charged ions is used to ionize the source gas. Such ion mixtures accelerated with the same accelerating voltage are particularly useful because they can provide a higher energy density than a singly charged ion beam. Therefore, they can reach a certain dose in a shorter amount of time. Multiply charged ions are also interesting because for the same accelerating voltage, the implantation depth they reach is greater than that of singly charged ions. The implantation energy (expressed in electron volts (eV)) is calculated by multiplying the charge of the singly charged ion or multiply charged ion by the accelerating voltage. Ion beams containing a mixture of singly charged ions and multiply charged ions are particularly useful because for a particular accelerating voltage, certain species (e.g., N 2+ ) will have a corresponding singly charged ion N +twice the implantation energy of the implantation layer. Therefore, a greater implantation depth can be achieved without increasing the acceleration voltage. According to an advantageous embodiment of the present invention, the positively charged ions preferably include a mixture of singly charged ions and / or multiply charged ions. For a given acceleration voltage, the ions are provided with an energy proportional to their charge, and the mixture of singly charged ions and multiply charged ions enables implantation in a wider depth range than singly charged ions in a single step. More advantageously, in the mixture of singly charged ions and multiply charged ions, the relative amount of differently charged ions decreases as the charge increases. Thus, the amount of implanted ions may decrease when moving from the coated substrate surface toward the body.
[0039] In an embodiment of the present invention, at least 90% of the ions in the ion beam consist of singly charged ions and doubly charged ions of species selected from N, O, He, Ne, Ar, Kr and the ratio of singly charged species to doubly charged species is at least 55 / 25. The corresponding singly charged species and doubly charged species are N + and N 2+ , O + and O 2+ 、He + and He 2+ 、Ne + and Ne 2+ ,Ar + and Ar 2+ .
[0040] In an alternative embodiment, the ions are implanted by sequentially implanting the selected ions as singly charged ions, for example in two or more steps at different accelerating voltages.
[0041] In a preferred embodiment of the invention, the temperature of the area of the glass substrate being processed beneath the area being processed is less than or equal to the vitrification coalescence temperature of silver. This temperature is affected, for example, by the ion current of the ion beam, the residence time of the area being processed in the ion beam, and any cooling means of the substrate.
[0042] In an advantageous embodiment of the invention, implantation ions of He, N or O are used, since they show less sputtering of the coating surface than heavier ions, which is particularly important for maintaining the integrity of the coating and its photodynamic properties. In another embodiment of the invention, implantation ions of N and O are combined.
[0043] In another advantageous embodiment of the invention, any implanted ions of Ar are used, since similar performance to implanted N ions can be achieved at a lower dose.
[0044] In one embodiment of the present invention, several ion implantation beams are used simultaneously or sequentially to process a glass substrate.
[0045] In one embodiment of the present invention, a total ion dose per surface unit area of the glass substrate is obtained by a single treatment via an ion implantation beam.
[0046] In another embodiment of the present invention, the total ion dose per surface unit area of the glass substrate is obtained by several consecutive treatments performed by one or more ion implantation beams. The ion beams can use the same or different source gases to implant the same or different ions of O, N, He, Ne, Ar or Kr.
[0047] The method of the present invention is preferably carried out in a vacuum chamber in a process comprising 10 -2 Millibar and 10 -7 mbar, more preferably at a pressure comprised between 5×10 -5 mbar and 6×10 -6 The pressure is between 1000 and 2000 mbar.
[0048] An exemplary ion source for carrying out the method of the invention is the Hardion+ ECR ion source from Ionics SA.
[0049] Advantageously, the ion implantation depth Dmax may be comprised between 0.1 μm and 1 μm, preferably between 0.1 μm and 0.5 μm. The implanted ions diffuse between the substrate surface and the implantation depth. The implantation depth may be adapted by selecting the implanted ions, by the acceleration energy, by the irradiation angle, and may vary to a certain extent depending on the substrate.
[0050] According to the present invention, the mixture of singly charged ions and multiply charged ions of O or N preferably comprises O + and O 2+ or N + 、N 2+ and N 3+ or Ar + and Ar 2+ .
[0051] According to a preferred embodiment of the present invention, the mixture of singly charged ions and multiply charged ions of O contains more than O + Smaller amounts of O 2+ In a more preferred embodiment of the present invention, the mixture of singly and multiply charged ions of O contains 55% to 98% O + and 2% to 45% O 2+ .
[0052] According to another preferred embodiment of the present invention, the mixture of singly charged ions and multiply charged ions of N contains more than N + and N 2+ Smaller amounts of N 3+In a more preferred embodiment of the present invention, the mixture of singly and multiply charged ions of N contains 40% to 70% of N + , 20% to 40% N 2+ , and 2% to 20% N 3+ .
[0053] According to another preferred embodiment of the present invention, the mixture of singly charged ions and multiply charged ions of Ar contains more than Ar + Smaller amounts of Ar 2+ In a more preferred embodiment of the present invention, the mixture of singly and multiply charged ions of Ar contains 50% to 80% of Ar + , 10% to 30% Ar 2+ , and 3% to 15% Ar 3+ .
[0054] The chemical durability of the coated glass substrates was tested using a climate chamber test and a salt spray test.
[0055] According to standard EN 1096-2012, the neutral salt spray test consists in subjecting the coated glass to a salt spray formed by distilled water with dissolved NaCl. The temperature conditions are 35° C. + / - 2° C. The test duration is 10 days.
[0056] Climate Chamber Test (CC): This test consists in placing the sample in a chamber filled with a water-saturated atmosphere of H2O and subjecting it to a temperature cycle of 2 hours each (during which the temperature changes from 45°C to 55°C and back to 45°C). The test duration is 10 days.
[0057] Salt spray test (NSST): This test consists in subjecting the specimen to the action of a salt spray formed by spraying an aqueous solution containing 50 g / l of sodium chloride in a chamber maintained at 35°C (full details of this test are set out in the international standard ISO 9227-2001) until the first defect appears.
[0058] Glass substrates A and B were implanted with ions. These glass sheets carried a coating deposited on the main surface by magnetron sputtering. The layer sequence of the coatings for the different substrates is detailed in Table 1 below.
[0059] Table 1
[0060] TZO is a mixed oxide of Ti and Zr, more preferably a titanium-zirconium mixed oxide with a weight ratio of TiO2 / ZrO2 of 65 / 35. SiN is Si3N4. All coatings are deposited on ordinary transparent soda-lime glass using magnetron sputtering. ZnO:Al is zinc oxide doped with aluminum.
[0061] The glass substrate was implanted with a mixture of singly charged ions and multiply charged ions of He, Ar, and N. The dose was 10 15 ions / cm 2 With 8×10 16 ions / cm 2 The current of the ion beam was varied between 2 and 10 mA. The accelerating voltage was 40 kV. The implanted substrates maintained electrical conductivity, as determined by measuring the sheet resistance with a contactless measuring device Stratometer G from Nagy Messsysteme GmbH. The implanted glass substrates were subjected to climate chamber and salt spray tests, and the number of defect sizes was determined.
[0062] Detailed test results after ion implantation of Ar ions in A and B are shown in Table 3. The test results are rated from 0 to 5, where 5 is no degradation and 1 is very severe degradation. Without implantation, A and B achieve a test rating of 1.
[0063] In addition, substrates A and B were implanted with He and N ions at the dose ranges and current ranges summarized in Table 3.
[0064] For all implanted samples, significant durability improvements were observed, especially the initial defects observed did not significantly expand in size during the aging test. Also on the ion implanted samples, cross-sectional TEM images showed the formation of silver nanoparticles in the dielectric coating above and below the silver functional layer of both substrates A and B. These nanoparticles were <10 nm away from the silver functional layer. The nanoparticles had a substantially circular cross-section and were estimated to be between 2 and 4 nm in diameter.
[0065] Table 2
[0066] Table 3
Claims
1. A glazing comprising a glass substrate (6) and comprising a coating (7) on at least one main surface of the glass substrate, the coating comprising n infrared radiation reflecting functional layers (2) containing silver and n+1 dielectric coatings (1, 3) arranged alternately, wherein n≥1, so that each functional layer is surrounded by the dielectric coating, wherein at least one dielectric coating is in direct contact with at least one infrared reflecting functional layer and contains silver nanoparticles (4, 5) having a diameter in the range of 1 to 5 nm at a distance of up to 10 nm from the at least one infrared reflecting functional layer.
2. The inlaid glass according to claim 1, wherein: The infrared radiation reflecting functional layer has a thickness of at least 6 nm and / or at most 22 nm.
3. The embedded glass according to claim 1, wherein: The coating has a total geometric thickness T of up to 300 nm.
4. Glazing according to any preceding claim, wherein: The glass substrate is selected from a soda-lime silicate glass substrate, a borosilicate glass substrate or an alumina silicate glass substrate.
5. Glazing according to any preceding claim, comprising implanted ions in the coating selected from the group consisting of ions of O, N, He, Ne, Ar and Kr.
6. The glazing according to claim 4, wherein: The implanted ions are positively charged ions.
7. The glazing according to any one of claims 4 and 5, wherein: The implanted ions are implanted into the coated glass substrate starting from the outer surface of the coating layer to a depth Dmax comprised between 0.1 μm and 1 μm.
8. The glazing according to any one of claims 4 to 6, wherein: The implanted ion dose range is 5×10 14 ions / cm 2 With 8×10 16 ions / cm 2 between.
9. A method for improving the corrosion resistance of a coated glass substrate, the method comprising: a. providing a glass substrate comprising a coating on a main surface, the coating comprising n infrared radiation reflecting functional layers comprising silver and n+1 dielectric coatings arranged alternately, wherein n≥1, such that each functional layer is surrounded by a dielectric coating, wherein at least one dielectric coating is in direct contact with at least one infrared reflecting functional layer; b. Providing a source gas selected from O2 or N2, He, Ne, Ar or Kr; c. ionizing the source gas to form positively charged ions of O, N, He, Ne, Ar or Kr; d. accelerating the positively charged ions of O, N, He, Ne, Ar or Kr with a certain accelerating voltage to form an ion beam, e. Positioning the glass substrate component in the trajectory of a beam of positively charged ions of O, N, He, Ne, Ar or Kr, wherein the coating faces the beam and setting the acceleration voltage to a value selected between 5 kV and 100 kV so as to implant the ions throughout the at least one infrared reflecting functional layer.
10. The method according to claim 8, wherein: In step c., the source gas is ionized to form positively charged ions.
11. The method according to any one of claims 8 and 9, wherein: In step c., the source gas is ionized to form a mixture of singly and multiply charged ions.
12. The method according to any one of claims 8 to 10, comprising, in step e., setting the accelerating voltage to a value comprised between 5 kV and 100 kV.
13. Use of ion implantation for improving the corrosion resistance of a glass substrate, the glass substrate comprising a coating on at least one main surface thereof, the coating comprising n infrared radiation reflecting functional layers containing silver and n+1 dielectric coatings arranged alternately, wherein n≥1, so that each functional layer is surrounded by a dielectric coating, wherein at least one dielectric coating is in direct contact with at least one infrared reflecting functional layer.